Optimizing the Northern Fortress as a Strategic Support for Indonesia’s New Import Gateway - Devaky Christiani somba; Agus Adriyanto; I wayan Warka; Tasdik Mustika Alam (CV. AFDIFAL MAJU BERKAH, 2026)
This study examines the optimization of military defense in North Sulawesi as a supporting pillar for Indonesia’s new import gateway. Positioned strategically on the Pacific rim, North Sulawesi is expected to become a hub for imported goods to support national economic equalization. However, this import route shift also brings security challenges, including military and non-military threats such as smuggling, maritime crimes, and potential infiltration by terrorist groups. This research employs a qualitative descriptive method based on literature study, focusing on the analysis of naval and air defense strategies, modernization of main weapon systems (alutsista), and the enhancement of human resources within the Indonesian National Armed Forces (TNI). The results indicate that strengthening defense infrastructure, including the addition of warships, patrol vessels, and modern fighter aircraft, is urgently needed to maintain regional stability. Furthermore, the application of the smart defense concept, integrating advanced technology with local community empowerment, can sustainably enhance maritime resilience. Investment in the defense sector has been shown to create a conducive climate for international trade, boost investor confidence, and strengthen Indonesia’s economic connectivity with the Asia-Pacific region. This study recommends synergy between the Ministry of Defense, TNI, and the national defense industry to accelerate the modernization and maintenance of alutsista, while ensuring the security of trade routes in North Sulawesi. With these measures, North Sulawesi can function optimally as a strategic import gateway that supports national economic growth and reinforces state defense